Indirect methodology for life-span estimation of power transformers from the evaluation of its dielectric materials - Acuña-Barrantes, Luis Diego (2020)
An adequate and reliable operation of the power transformers in the electrical networks constitutes a determining factor in the continuity of service, which justifies its attention in the evolution of its integrity, defined by its dielectric system mainly conform by oil and paper. The research focused on the analysis of chemical tests applied to a group of 10 MVA power transformers with different periods of operation and their correlation with the actual aging estimated by the Degree of Polymerization (DP) and 2-furaldehyde (2-FAL), in addition to mechanical stress tests applied to the dielectric paper. This stress, measured in the dielectric paper, presented a reduction of 74.49% with respect to the minimum value established by the IEC (80 MPa) and a DP of 88.4. The operating conditions of each transformer along with the percentage of humidity of the dielectric paper, the total and Oxygen gases measured in ppm, allowed the estimation of 2-FAL indirectly. The approximate results of the Degree of Polymerization were enough for its evaluation as a “slightly aged” condition. So, the approximation of the maximum life-span was 27 years. This estimate is consistent with the low levels of measured combustible gases (less than 700 ppm) and Oxygen.